The role of materialism in predicting compulsive buying among University Students in Klang Valley, Malaysia - Hashim, Aisyah Hazwani; Marof, Aini Azeqa; Zaremohzzabieh, Zeinab (Human Resource Management Academic Research Society, 2023)
Given the rising concerns over mental health and consumer behavior among young adults, this study is crucial in understanding the factors that contribute to compulsive buying among university students in Klang Valley, Malaysia, a subject that has implications for long-term financial and psychological well-being. Thus, this study aims to explore the relationship between depression, materialism, and excessive Internet use with compulsive buying behavior among university students in Klang Valley, Malaysia. Using homogenous convenience sampling, 307 respondents were selected to participated in this study that involved university students from selected public and private universities in Klang Valley area. The data were gathered through a self-administered questionnaire employing established scales for measuring each variable. Statistical analyses included descriptive statistics, independent t-tests, Pearson correlation, and multiple regression. The results show that the majority of the respondents exhibited moderate levels of depression, materialism, excessive Internet use, and compulsive buying. Notably, male students showed higher levels of depression than their female counterparts, while female students displayed greater excessive Internet use. Among the variables examined, materialism and excessive Internet use were found to positively correlate with compulsive buying behavior. Multiple regression analysis indicated that materialism was the strongest predictor of compulsive buying, followed by excessive Internet use. The study concludes that both materialism and excessive Internet use significantly influence compulsive buying among university students in Klang Valley, Malaysia. Understanding these relationships can inform interventions aimed at minimizing compulsive buying behavior, thereby promoting a healthier lifestyle for university students.